Gauging to explore interlinkages between green and sustainable foreign investment, economic complexity, and environmental performance in Vietnam - Nguyet, Pham Thi Anh (International Journal of Innovative Research and Scientific Studies, 2025)
We use a model-free connectedness approach to discover some links among green FDI, economic complexity, CO2 outputs, and energy productivity in Vietnam from 1995 to 2022. Our findings make the correlation between green FDI and economic complexity evident throughout the study. The overall net connectivity displays that green FDI was a primary net recipient of shock waves before 2009 and during the 2019-2022 period, but then turned into a net shock emitter from 2010 to 2015. Economic complexity was the main net receiver of spillover shocks before 2014, but it turned into a net shock transmitter thereafter, except for 2017. Pairwise directional connectivity in the net indicates that green FDI commanded economic complexity throughout the examined period, except for the 2002-2005, 2015-2017, and 2019-2022 periods. The development of economic complexity in Vietnam faces many difficulties when the flow of green FDI decreases.